Prevalence and Risk Factors of Chronic Kidney Disease in Hypertensive Patients attended at Victoria Chitepo Provincial Hospital Mutare Zimbabwe, 2022 - Salissou, M.T. Mahamane; Shumba, T.; Olivier, S. Makengo; Yacoubou, A.R. Mahaman (International Journal of Scientific Research in Biological Sciences, 2023)
Hypertension and chronic kidney disorders (CKD) are key public health burdens in Zimbabwe .In this study we evaluate the prevalence and risk factors of CKD in hypertensive patients attended at Victoria Chitepo Provincial Hospital in Mutare from July to October 2022.This was an analytical cross sectional study which investigated in a retrospective manner the medical records of patients with hypertension to determine those who developed CKD. The clinical characteristics and GFR were used to determine the stage of CKD. Random sampling method was used to choose 220 participants from the biochemistry results book to get Urea and electrolytes test results, age, race, gender, location of residence, whether patient had diabetes mellitus and on any antihypertensive medication .Out of 220 cases 71 (32.3%) had developed CKD at different stages as follow : 16.9% in stage 1, 22.5% in stage 2, 49.3% in stage 3, 7.1% in stage 4 and 4.2% were in stage 5. Furthermore 39 (55%) were female and 32 (45%) male. 11(15.5%) participants were below 30 years old, 23 (32.4%) were between the ages of 30 and 50 and 37 (52.1%) participants were over 50 years old. Of the 71 participants, 100% were all black. About 28 cases (39.4%) of the participants also had Diabetes Mellitus. 23 (32.4%) participants were not on any antihypertensive drugs. 22.5% were from the rural areas, 32.4% were from semi-urban areas and 45.1% were from urban areas. Risk factors analysis indicated statistical significance between Hypertension induced CKD with regards to gender OR 1.96 CI (1.09- 3.51), P=0.023, History of diabetes mellitus OR 2.58 CI (1.38-4.81), P= 0.0024, History of antihypertensive medication OR 0.46, CI (0.24-0.88), P= 0.018.There is high burden of CKD among patients with hypertension in this study. Gender, Increasing age, Race, diabetes mellitus and use of antihypertensive drugs and location of residence are significantly associated with CKD in hypertensive patients.